Blended vs. Online Discovery Learning: Enhancing Students' Critical Thinking Skills - Eky Billy Revanda; Hadi Soekamto; TAN Geok Chin Ivy (Future Space: Studies in Geo-Education, 2026)
This study investigates the comparative efficacy of Blended Discovery Learning (BDL) versus fully Online Discovery Learning (ODL) in fostering critical thinking skills within geography education. Amidst the rapid digitalization of pedagogy, the structural resilience of inquiry-based models across varying delivery configurations remains a critical concern. Utilizing a quasi-experimental approach with a nonequivalent posttest-only control group design, this research employed the geographic theme of cultural preservation in Malang City as a complex spatial stimulus for student inquiry. Participants were selected via randomized assignment from a homogenous student population to ensure baseline equivalency in geographic proficiency. Data were elicited through a validated essay instrument comprising five higher-order thinking indicators and analyzed using Independent Sample T-Tests. Statistical analysis yielded a significance value of p = 0.071; however, subsequent Cohen’s d calculation revealed a moderate effect size (d = 0.43), indicating a marginal pedagogical advantage for the blended discovery configuration. These findings suggest that while both modalities are robust, the hybrid approach provides a slightly more intensive scaffolding for geographic reasoning. Crucially, the results imply that the inherent constructivist nature of the Discovery model maintains its functional integrity across diverse digital environments, offering significant pedagogical flexibility. This study contributes to the discourse on hybrid geography education by demonstrating that the choice of instructional platform while influential does not compromise the core cognitive benefits of discovery-based inquiry.